Designing Character Design in the Illustrated Story Book "The Mystery of Ilange Klambi Si Besut" - Khalaya Azizah Wibowo; Masnuna; Aninditya Daniar (Judikatif: Jurnal Desain Komunikasi Kreatif, 2025)
Indonesia is rich in cultural diversity, one of which includes local theatrical arts such as Besutan from Jombang Regency. Besutan is a form of traditional folk drama that became the forerunner of Ludruk, yet it now faces challenges due to the lack of younger generations to carry it on and limited educational media to promote it. Therefore, introducing this art form, especially to elementary school children, is essential through educational, engaging, and easy-to-understand media such as illustrated storybooks. To support this effort, the Besutan performing arts are introduced through an interactive picture book specifically designed for children. In Besutan performing arts, there are four main characters involved. These characters represent cultural values while also being visually appealing due to their distinctive costumes and behaviors. The portrayal of each character is adjusted to match their personality traits and the symbolic meanings embedded in their visual elements.This study aims to develop a visual character design that embodies the cultural traits of Besutan in a way that is attractive to children. The character design process includes observing local culture, conducting interviews with Besutan performers, and studying visual traits of stage characters. The outcome supports the development of an interactive and educational storybook that effectively introduces local performing arts to children.